Reversal of cardiopulmonary exercise intolerance in patients with post-thrombotic obstruction of the inferior vena cava. Issue 208 (December 2021) - Sebastian, Tim; Barco, Stefano; Kreuzpointner, Robert; Konstantinides, Stavros; Kucher, Nils
Abstract: Background: It is unclear whether cardiopulmonary exercise intolerance in patients with chronic obstruction of the inferior vena cava (IVC) is reversible following endovascular IVC reconstruction. Methods: In 17 patients (mean age 45 ± 15 years, 71% men) with post-thrombotic syndrome due to IVC obstruction and preserved left ventricular ejection fraction (mean 58 ± 3%), we performed cardiopulmonary exercise testing before and 3 months after IVC reconstruction (mean 4.1 ± 1.5 implanted stents). The median time from latest episode of deep vein thrombosis to intervention was 150 (interquartile range 102–820) days. Results: At baseline, 12 (71%) patients reported New York Heart Association (NYHA) class II or III symptoms, 76% did not achieve >85% of predicted oxygen uptake at peak exercise (mean 61.8 ± 13.7%). After IVC reconstruction, the following changes were observed at anaerobic threshold: work rate increased by 14.6 W, 95%CI (−0.7; 30.0), oxygen uptake increased by 1.8 ml/kg, 95%CI (0.3; 3.3). Oxygen pulse increased by 1.95 ml per beat, 95%CI (1.12; 2.78), corresponding to a mean relative increase of 22.5%, 95%CI (12.4; 32.7) ( p < 0.001). The following changes were observed at peak exercise: work rate increased by 48.1 W, 95%CI (27.8; 68.4), oxygen uptake increased by 6.4 ml/kg, 95%CI (3.8; 9.1). Oxygen pulse increased by 2.68 ml per beat, 95%CI (1.60; 3.76), corresponding to a mean relative increase of 29.4%, 95%CI (17.7; 41.2) ( p < 0.001). At follow-up, 5 (29%) patients remained in NYHA class II. Conclusions: In patients with chronic IVC obstruction, cardiopulmonary exercise intolerance as a result of impaired cardiac filling is at least partially reversible following endovascular IVC reconstruction. Study registration: URL: https://clinicaltrials.gov . Unique identifier: NCT02433054 . Highlights: Obstruction of the inferior vena cava is associated with cardiopulmonary exercise intolerance. We performed cardiopulmonary exercise testing before and 3 months after inferior vena cava reconstruction in 17 patients with post-thrombotic syndrome due to inferior vena cava obstruction and preserved left ventricular ejection fraction. After IVC reconstruction, work rate, oxygen uptake and oxygen pulse increased at anaerobic threshold as well as at peak exercise. In patients with chronic inferior vena cava obstruction, cardiopulmonary exercise intolerance resulting from impaired cardiac filling is at least partially reversible following endovascular IVC reconstruction.